Genotoxicity of Esentai and Ulken Almaty rivers water on animal test-systems (Eurasian Journal of Ecology, 2021)
Ecological monitoring, including water resources, is included in a set of measures for the rational use and protection of the environment. Currently, the assessment of water resources' genotoxicity and mutagenicity is an essential component of ecological monitoring.This research aimed to investigate water's genotoxicity from the Esentai and Ulken Almaty rivers flowing in Almaty. It was established that the content of Fe, Cu, Co, Ni, Pb, and Cd in the Almaty rivers water does not exceed the maximum permissible concentration (MPC). In contrast, zinc content in the Esentai and Ulken Almaty rivers' water exceeded the MPC, respectively, by 1.1 and 7.7-folds, manganese – 2.1, and 1.9-folds. It was found that water samples from the Esentai and Ulken Almaty rivers showed a DNA-damaging effect on the studied cells (bone marrow, liver, kidneys, and spleen) of laboratory mice. In the cells of the studied organs in the experimental groups, the frequency of single-strand DNA breaks a statistically significant increase compared to the control group's animal. The genotoxic action's organospecificity of the studied river waters on laboratory mice was established. According to their sensitivity to water's genotoxic effect, experimental mice's organs can arrange in the following order: spleen and bone marrow> liver> kidneys. An increase in lipid peroxidation products was found in the laboratory mice' liver that drank water from the Esentai and Ulken Almaty rivers. Thus, the results of the physicochemical, molecular-genetic, and biochemical analysis of water on animal test objects indicate the presence in the investigated natural surface waters of chemicals with genotoxic and toxic activity.Keywords:surface waters; heavy metals; DNA comet assay, organ specificity, lipid peroxidation